Metformin promotes in vitro maturation of oocytes from aged mice by attenuating mitochondrial oxidative stress via SIRT3-dependent SOD2ac - Yongzhi Cao; Yongzhi Cao; Yongzhi Cao; Yongzhi Cao; Yongzhi Cao; Yongzhi Cao; Yongzhi Cao; Zhao Wang; Zhao Wang; Zhao Wang; Zhao Wang; Zhao Wang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Human female fecundity decreases irreversibly as chronological age rises, adversely affecting oocyte quality, consequently worsening pregnancy outcomes and increasing the extent of birth defects. The first-line type 2 diabetes treatment metformin has been associated with delayed aging and reduction of oxidative stress; yet it remains unclear if metformin confers any benefits for oocytes from aged mice, particularly in the context of the assisted human reproductive technology (ART) known as in vitro maturation (IVM). Here, we found that adding metformin into the M16 culture medium of oocytes from aged mice significantly improved both oocyte maturation and early embryonic development. This study showed that metformin reduced the extent of meiotic defects and maintained a normal distribution of cortical granules (CGs). RNA-seq analysis of metformin-treated oocytes revealed genes apparently involved in the reduction of mitochondrial ROS. Further, the results supported that the metformin improved mitochondrial function, reduced apoptosis, increased the extent of autophagy, and reduced mitochondrial ROS via SIRT3-mediated acetylation status of SOD2K68 in oocytes from aged mice. Thus, this finding demonstrated a protective effect for metformin against the decreased quality of oocytes from aged mice to potentially improve ART success rates and illustrated a potential strategy to prevent or delay reproductive aging.